The benefits and risks of Echinacea in treatment of common cold and influenza - Yenny, Yenny; Djanun, Zunilda (Universa Medicina, 2008)
The common cold is one of the worldâs most prevalent illnesses in adults and children. This upper respiratory tract infection is caused by different kinds of agents. Effects on health, well-being, and productivity are significant. Preparations made from plants of the genus Echinacea are widely used for the prevention and treatment of colds. Three species of Echinacea used for medicinal purposes are Echinacea purpurea, Echinacea angustifolia, and Echinacea pallida. The beneficial effects of Echinacea are thought to be due to its immunomodulatory activity, most notably activation of macrophages, polymorphonuclear leukocytes and natural killer cells. Many clinical trials, including a number of blind randomized trials, have reported health benefits. Although these studies show beneficial effects, recommendations on Echinacea use cannot be made due to lack of product standardization and variability in dosage, sample size and methodological quality used in the trials. Therefore, well-designed studies with consistent standardized measures are required for assessment of the efficacy of Echinacea in treatment of common cold and influenza.